Method for preparing sodium-ion battery positive electrode material, sodium-ion battery positive electrode material and application of sodium-ion battery positive electrode material

By preparing and grading the sodium ion battery positive electrode material with a specific particle size range, the problem of insufficient compaction density in the prior art is solved, and the improvement of battery performance and the expansion of application scenarios is achieved.

CN119650681APending Publication Date: 2025-03-18SHANXI HUANA COPPER ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411992484.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The compaction density of existing sodium ion battery positive electrode materials is insufficient, which affects the specific capacity, efficiency, internal resistance and cycle life of the battery, making it difficult to adapt to a variety of application scenarios.

Method used

By preparing material 1 with a Dv50 particle size range of 10-12 μm and material 2 with a 5.1-7.5 μm, and grading the particle size according to the mass ratio, a high compaction density sodium ion battery positive electrode material was obtained.

Benefits of technology

The compaction density of the positive electrode sheet of the sodium ion battery is improved, the volume energy density, cycle retention rate and life of the battery cell are improved, and the experimental cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650681A_ABST
    Figure CN119650681A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium-ion battery positive electrode materials, in particular to a method for preparing a sodium-ion battery positive electrode material, the sodium-ion battery positive electrode material and application of the sodium-ion battery positive electrode material. The method comprises the following steps: (a) preparing a material 1 with a Dv50 particle size range of 10-12 [mu] m; (b) substituting the Dv50 particle size and the average area enveloping degree of the material 1 into a model formula, and calculating to obtain a material 2 with the Dv50 particle size range of 5.1-7.5 microns; (c) preparing a material 2 with a Dv50 particle size range of 5.1-7.5 [mu] m; (d) carrying out grain size distribution on the prepared material 1 and material 2 according to a mass ratio; and (e) carrying out grain size distribution on the material 1 and the material 2 to obtain the sodium ion battery positive electrode material. The sodium-ion battery positive electrode material prepared by the method not only can improve the compaction density of a sodium-ion battery positive electrode plate, but also can improve the volume energy density of a battery cell, the cycle retention rate of the battery cell and the service life of the battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery positive electrode, and in particular to a method for preparing a sodium ion battery positive electrode material, a sodium ion battery positive electrode material and applications thereof. Background Art

[0002] The compaction density is crucial to the performance of sodium-ion batteries, and it affects the specific capacity, efficiency, internal resistance, and cycle life of the battery pole piece. Increasing the compaction density is conducive to improving the capacity and energy density of sodium-ion batteries, making sodium-ion batteries adaptable to more application scenarios, such as 3C digital products, consumer products, and small power products. Therefore, in the battery design and manufacturing process, the compaction density of the positive pole piece of the sodium-ion battery is improved through process optimization without over-pressuring.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The first object of the present invention is to provide a method for preparing a positive electrode material for a sodium ion battery. The positive electrode material for a sodium ion battery prepared by the method can not only improve the compaction density of the positive electrode sheet of the sodium ion battery, but also improve the volume energy density of the battery cell, the cycle retention rate of the battery cell and the life of the battery cell.

[0005] The second object of the present invention is to provide a positive electrode material for a sodium ion battery.

[0006] The third object of the present invention is to provide a method for preparing a positive electrode material for a sodium ion battery or the use of a positive electrode material for a sodium ion battery in preparing a positive electrode sheet and a sodium ion battery.

[0007] To achieve the above object, the technical solution of the present invention is implemented as follows: a method for preparing a positive electrode material for a sodium ion battery, the method for preparing a positive electrode material for a sodium ion battery comprises the following steps:

[0008] (a) preparing material 1 with a Dv50 particle size range of 10-12 μm;

[0009] (b) Substituting the Dv50 particle size and average area envelope of material 1 into the model formula, the material 2 with a Dv50 particle size range of 5.1-7.5 μm is calculated;

[0010] (c) preparing material 2 with a Dv50 particle size range of 5.1-7.5 μm;

[0011] (d) performing particle size grading on the prepared material 1 and material 2 according to a mass ratio;

[0012] (e) After completing the particle size grading of material 1 and material 2, a positive electrode material for a sodium ion battery is obtained.

[0013] Preferably, in step (b), the model formula for calculating the Dv50 particle size of material 2 based on the Dv50 particle size of material 1 is as follows:

[0014]

[0015] Among them, Dv50 材料1 The 50% median of the volume-accumulated particle size distribution of Material 1, tested using Malvern 3000; Dv50 材料2 The 50% median of the volume cumulative particle size distribution of representative material 2 was tested using Malvern 3000; the average area envelope of material 1 was tested using Keyence VHX-X1; k is the model coefficient, and the k range is 0.5-2.

[0016] Preferably, in step (d), the mass ratio of the particle size distribution of material 1 to material 2 is 5:5-9:1.

[0017] Preferably, after the positive electrode sheet is made from the positive electrode material of the sodium ion battery in step (e), the compaction density of the positive electrode sheet is 3.29-3.38 g / cm 3 .

[0018] Preferably, the process of preparing material 1 in step (a) comprises:

[0019] a1) performing a first sintering of the raw materials containing Na, Cu, Fe and Mn elements at 850-920° C. for 6-20 hours, and then performing a first crushing to obtain a sintered material with a particle size of 5 μm ≤ Dv50 ≤ 8 μm;

[0020] a2) performing a second sintering on the sintered material at 910-940° C. for 6-20 hours at a constant temperature, and then performing a second pulverization to obtain a sodium ion battery positive electrode material with a particle size of 10 μm ≤ Dv50 ≤ 12 μm, that is, obtaining material 1.

[0021] Preferably, the process of preparing material 2 in step (c) comprises:

[0022] c1) performing a first sintering of the raw materials containing Na, Cu, Fe and Mn elements at 850-920° C. for 6-20 hours, and then performing a first crushing to obtain a sintered material with a particle size of 5 μm ≤ Dv50 ≤ 8 μm;

[0023] c2) performing a second sintering on the sintered material at 880-910° C. for 6-20 hours, and then performing a second pulverization to obtain a sodium ion battery positive electrode material with a particle size of 5.1 μm ≤ Dv50 ≤ 7.5 μm, that is, obtaining material 2.

[0024] Preferably, the raw material containing Na, Cu, Fe and Mn elements in step a1) or c1) also includes element A; the element A includes one or more of Li, Ni, Mg, Zn, Co, Al, Zr and Ti.

[0025] Preferably, the general formula of the sodium ion battery positive electrode material of material 1 in step a2) is Na a Cu x Fe y Mn z A 1-x-y- z O2, wherein A includes one or more of Li, Ni, Mg, Zn, Co, Al, Zr, Ti; 0.5<a≤1.1, 0.1≤x≤≤0.3, 0<y≤0.5, 0<z≤0.5, 0<1-xyz≤0.5.

[0026] Preferably, the present invention further provides a sodium ion battery positive electrode material prepared by the method for preparing a sodium ion battery positive electrode material.

[0027] Preferably, the present invention also provides a method for preparing a positive electrode material for a sodium ion battery or the use of the positive electrode material for a sodium ion battery in preparing a positive electrode sheet and a sodium ion battery.

[0028] The beneficial effects of the present invention are embodied in:

[0029] (1) The method provided by the present invention is applicable to single crystal sodium ion battery positive electrode materials, and can quickly and accurately obtain the particle size range of two materials with particle size distribution, thereby reducing the number of experiments to determine the optimal compaction density of the sodium ion battery positive electrode sheet, thereby reducing the experimental cost.

[0030] (2) The sodium ion battery positive electrode material prepared by the method provided by the present invention can improve the compaction density of the sodium ion battery positive electrode sheet. Under the same pressure, the compaction density can be increased by 5.96%, thereby improving the volume energy density of the battery cell.

[0031] (3) The sodium ion battery positive electrode material prepared by the method provided by the present invention can improve the compaction density of the sodium ion battery positive electrode sheet, and is verified on a laminated soft-pack battery. Not only is the cycle retention rate of the battery significantly improved, but it can be seen from the slope of the capacity retention rate that the battery life is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 This is a full electric cycle test chart of the batteries prepared in Comparative Example 1, Comparative Example 2 and Implementation 1 to Example 5 of the present invention. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the comparative examples. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0035] Example

[0036] In a first aspect, the present invention provides a method for preparing a positive electrode material for a sodium ion battery, the method comprising the following steps:

[0037] (a) Preparation of material 1 with a Dv50 particle size range of 10-12 μm.

[0038] The process of preparing material 1 in step (a) comprises:

[0039] a1) performing a first sintering of the raw materials containing Na, Cu, Fe and Mn elements at 850-920° C. for 6-20 hours at a constant temperature, and then performing a first crushing to obtain a sintering material with a particle size of 5 μm ≤ Dv50 ≤ 8 μm;

[0040] a2) performing a second sintering on the sintered material at 910-940° C. for 6-20 hours at a constant temperature, and then performing a second pulverization to obtain a sodium ion battery positive electrode material with a particle size of 10 μm ≤ Dv50 ≤ 12 μm, that is, obtaining material 1.

[0041] (b) Substituting the Dv50 particle size and average area envelope of material 1 into the model formula, the material 2 with a Dv50 particle size range of 5.1-7.5 μm was calculated.

[0042] The model formula for calculating the Dv50 particle size of material 2 based on the Dv50 particle size of material 1 in step (b) is as follows:

[0043]

[0044] Among them, Dv50 材料1 The 50% median of the volume-accumulated particle size distribution of Material 1, tested using Malvern 3000; Dv50 材料2 The 50% median of the volume cumulative particle size distribution of representative material 2 was tested using Malvern 3000; the average area envelope of material 1 was tested using Keyence VHX-X1; k is the model coefficient. Due to differences in sintering temperature, sintering time, crushing method, etc., different process conditions will have different model coefficients, and the k range is 0.5-2.

[0045] The present invention proposes this formula because after the material particles are densely packed, there will be gaps between the particles, especially for materials with larger particle sizes and narrower particle size spans, the gaps between the particles after dense packing will be larger, which seriously affects the compaction density of the material. Filling the gaps with small particles can improve the compaction density, and because the morphology of single crystal particles is not all perfect spheres, it is necessary to introduce the average area envelope and the model coefficient k, and obtain the best particle size grading particle size and coefficient k according to the actual morphology of the particles. When the introduced particles are too large, the effect of particle size grading to improve compaction cannot be achieved. When the introduced particles are too small, they also cannot fill the gaps between large particles. Moreover, because small particles have a larger specific surface area and a larger surface energy, the dispersion effect of the slurry may be reduced, the weak agglomeration between particles may increase, and the side reactions of the material may increase during operation.

[0046] (c) Prepare material 2 with a Dv50 particle size range of 5.1-7.5 μm.

[0047] The process of preparing material 2 in step (c) comprises:

[0048] c1) performing a first sintering of the raw materials containing Na, Cu, Fe and Mn elements at 850-920° C. for 6-20 hours at a constant temperature, and then performing a first crushing to obtain a sintering material with a particle size of 5 μm ≤ Dv50 ≤ 8 μm;

[0049] c2) The sintered material is subjected to a second sintering at 880-910° C. for a constant temperature sintering time of 6-20 hours, followed by a second pulverization to obtain a sodium ion battery positive electrode material with a particle size of 5.1 μm ≤ Dv50 ≤ 7.5 μm, i.e., obtaining Material 2.

[0050] (d) performing particle size distribution on the prepared material 1 and material 2 according to a mass ratio. In step (d), the mass ratio of the particle size distribution of material 1 and material 2 is 5:5-9:1.

[0051] (e) After completing the particle size grading of material 1 and material 2, a positive electrode material for a sodium ion battery is obtained.

[0052] The raw material containing Na, Cu, Fe and Mn elements in step a1) or c1) also includes element A; element A includes one or more of Li, Ni, Mg, Zn, Co, Al, Zr and Ti. The general formula of the sodium ion battery positive electrode material of material 1 in step a2) is Na a Cu x Fe y Mn z A 1-x-y-z O2, wherein A includes one or more of Li, Ni, Mg, Zn, Co, Al, Zr, Ti; 0.5<a≤1.1, 0.1≤x≤≤0.3, 0<y≤0.5, 0<z≤0.5, 0<1-xyz≤0.5.

[0053] In some specific embodiments, the first pulverization includes any pulverization method commonly used in the art, such as mechanical pulverization, air flow pulverization or impact crushing, etc., and the present invention is not limited thereto.

[0054] In some specific embodiments, taking air flow crushing as an example, the feeding frequency of the first crushing is 5-20Hz, the crushing pressure is 0.2-0.6MPa, the classification frequency is 10-30Hz, and the induced draft frequency is 30-60Hz; taking mechanical crushing as an example, the feeding frequency of the first crushing is 15-25Hz, the classification frequency is 30-45Hz, the crushing frequency is 20-33Hz, and the induced draft frequency is 30-45Hz.

[0055] In some specific embodiments, the second pulverization includes any pulverization method commonly used in the art, such as mechanical pulverization, air flow pulverization or impact crushing, etc., and the present invention is not limited thereto.

[0056] In some specific embodiments, taking air flow crushing as an example, the feeding frequency of the second crushing is 5-20Hz, the crushing pressure is 0.2-0.6MPa, the classification frequency is 10-30Hz, and the induced draft frequency is 30-60Hz; taking mechanical crushing as an example, the feeding frequency of the second crushing is 15-25Hz, the classification frequency is 30-45Hz, the crushing frequency is 20-33Hz, and the induced draft frequency is 30-45Hz.

[0057] In a second aspect, the present invention provides a sodium ion battery positive electrode material, which is mainly prepared by the above-mentioned method for preparing a sodium ion battery positive electrode material.

[0058] The use of this sodium-ion battery positive electrode material can improve the compaction density of the positive electrode sheet, thereby improving the electrochemical performance of the battery, allowing the sodium-ion battery to adapt to more application scenarios, meet more customer needs, and increase product competitiveness.

[0059] In a third aspect, the present invention provides the method for preparing the above-mentioned positive electrode material for a sodium ion battery or the use of the above-mentioned positive electrode material for a sodium ion battery in preparing a positive electrode sheet and a sodium ion battery.

[0060] The above method for preparing positive electrode materials for sodium ion batteries can be used for the preparation of positive electrode sheets and sodium ion batteries. The positive electrode materials for sodium ion batteries obtained by this method can be directly used as positive electrode sheets and positive electrode active materials for sodium ion batteries, and can also be used in combination with other materials.

[0061] The sodium ion battery containing the above-mentioned sodium ion battery positive electrode material has excellent electrochemical performance.

[0062] Comparative Example 1

[0063] According to step (a) of the above method, a material 1 with a Dv50 particle size of 11.65 μm is prepared as comparative example 1; the preparation method of this comparative example is as follows:

[0064] a1) According to Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 Ni 2 / 9 The molar ratio of (OH)2 to sodium is 1:1. 1 / 9 Fe 1 / 3 Mn 1 / 3 Ni 2 / 9 After (OH)2 and Na2CO3 are mixed evenly, the first sintering is carried out at 860°C in an oxygen atmosphere, and the constant temperature sintering time is 15 hours. After cooling, the first sintered material is crushed by a cyclone pulse dust suction micro-crusher, wherein the feeding frequency is 20Hz, the mechanical crushing frequency is 30Hz, the grading frequency is 40Hz, and the induced draft frequency is 40Hz, and the Dv50 particle size = 5.27μm is obtained.

[0065] a2) In an oxygen atmosphere, the sintered material obtained in step a1) is subjected to a second sintering at 940° C. for 15 h. After cooling, the second sintered material is subjected to a second pulverization by a cyclone pulse dust suction micro-pulverizer, wherein the feeding frequency is 20 Hz, the mechanical pulverization frequency is 30 Hz, the classification frequency is 40 Hz, and the induced draft frequency is 40 Hz, to obtain a sodium ion battery positive electrode material NaCu with a Dv50 particle size of 11.65 μm. 1 / 9 Fe 1 / 3 Mn 1 / 3 Ni 2 / 9 O2, that is, obtain material 1.

[0066] Comparative Example 2

[0067] According to the particle size distribution method in the above method, assuming that the model coefficient is 1, and taking the Dv50 of material 1 in comparative example 1 as 11.65 μm and the average area envelope of material 1 as 77.8%, the Dv50 of material 2 is calculated as 5.48 μm in step (b) of the above method;

[0068] Material 2 with a Dv50 particle size of 5.48 μm was prepared as Comparative Example 2;

[0069] The preparation method of this comparative example is basically the same as that of comparative example 1, except that the temperature of the second sintering is replaced with 880°C.

[0070] A sodium ion battery positive electrode material with a Dv50 particle size of 5.48 μm was obtained, namely material 2.

[0071] Example 1-Example 5

[0072] According to step (d) in the above method, the materials 1 and 2 obtained in the above comparative examples 1 and 2 are graded according to mass ratios of 9:1, 8:2, 7:3, 6:4 and 5:5, respectively, and the particle size distribution design table 1 of implementation 1 to embodiment 5 is obtained.

[0073] Table 1 Particle size distribution design table

[0074] experiment Materials used Particle size distribution (mass ratio) Comparative Example 1 Material 1 Comparative Example 2 Material 2 Example 1 Material 1, Material 2 Material 1: Material 2 = 9:1 Example 2 Material 1, Material 2 Material 1: Material 2 = 8:2 Example 3 Material 1, Material 2 Material 1: Material 2 = 7:3 Example 4 Material 1, Material 2 Material 1: Material 2 = 6:4 Example 5 Material 1, Material 2 Material 1: Material 2 = 5:5

[0075] Test Characterization:

[0076] According to step (e) of the above method, the materials of comparative example 1, comparative example 2 and implementation 1 to example 5 in the above Table 1 are subjected to characterization tests: the particle size, specific surface area and tap density of material 1 and material 2 and implementation 1 to example 5 are tested, and the first-week discharge capacity and discharge efficiency of material 1 and material 2 and implementation 1 to example 5 are tested using CR2023 button batteries.

[0077] The button cell was prepared by using the sodium ion battery positive electrode materials prepared in each embodiment and the comparative example as positive electrode active materials, respectively, and preparing the button cell according to the following method: 0.45 g of positive electrode active material, 0.025 g of conductive carbon black SP and 0.025 g of polyvinylidene fluoride glue (mass fraction 10%, solvent N-methylpyrrolidone) were uniformly mixed, and then N-methylpyrrolidone was added to prepare a viscous slurry, and the slurry was coated on an aluminum foil (thickness 16 μm), and then baked in a vacuum drying oven at 120° C. for 12 hours to obtain a positive electrode sheet (active material surface density 5 mg / cm 2). Then, a metal sodium sheet was used as the counter electrode (300 μm thick), a glass fiber (waterman) was used as the diaphragm (675 μm thick), and a NaPF6 solution (the solvent was a mixture of EC and DMC, and the volume ratio was EC / DMC=1:1) (Alfa) with a sodium ion concentration of 1 mol / L was used as the electrolyte, and a 2032 button cell was assembled in an Ar atmosphere protection glove box. Each button cell was placed at 25°C, charged to 4.0V at a constant current of 0.1C, and then charged at a constant voltage until the current was less than or equal to 0.01 mA, and then stood for 5 minutes, and the charge capacity was recorded as the first charge capacity C0, and then discharged to 2.5V at a constant current of 0.1C, and the discharge capacity was recorded as the first discharge capacity D0, and the first discharge capacity D0 / first charge capacity C0×100% was the first coulomb efficiency. The results of the first discharge capacity and the first coulomb efficiency are shown in Table 2. Table 2 of the physical, chemical and electrical properties of Comparative Example 1, Comparative Example 2 and Implementation 1 to Implementation Example 5 was obtained.

[0078] Table 2 Physical and chemical properties and electrical properties:

[0079]

[0080] As shown in Table 2 above, Comparative Example 1 uses material 1, and the Dv50 particle size after crushing is 11.65 μm, and Comparative Example 2 uses material 2, and the Dv50 particle size after crushing is 5.48 μm. Examples 1-5 correspond to particle size distributions of 9:1, 8:2, 7:3, 6:4 and 5:5, respectively.

[0081] It can be seen from Table 2 that material 1 has a large particle size, a small specific surface area, and a high tap density, while material 2 has a small particle size, a large specific surface area, and a low tap density.

[0082] After the particle size grading, it can be seen from Example 1 to Example 5 that as the mass ratio of material 2 increases, the particle size after particle size grading gradually decreases, the specific surface area increases, and the tap density decreases.

[0083] According to step (e) of the above method, the materials of comparative example 1, comparative example 2 and implementation 1 to implementation example 5 in the above Table 2 are all made into pole pieces with a width of 200 mm, and a DYG-703B-Φ300mm*350mm / 100T roller press is used. The same rolling pressure, i.e., 30 tons, is used to roll the above 7 groups of pole pieces. After rolling, the compaction density of the pole pieces is tested, and the compaction density Table 3 is obtained.

[0084] Table 3 Compacted density

[0085]

[0086] It can be seen from Table 3 above that the compacted density of Experiment 3 increased from 3.19 g / cm 3Increased to 3.38g / cm 3 , the compaction density increased by 5.96%. In Experiment 4, the pole piece peeling force increased from 3.686N / mm to 4.156N / mm, and the pole piece peeling force increased by 12.8%.

[0087] Full electrical cycle test:

[0088] To control the variables, the same compaction density is used in all electric cycles, and Comparative Example 1 and Comparative Example 2 use 3.2 g / cm 3 The compacted density of Examples 1-5 is 3.35 g / cm 3 The compaction density of the negative electrode sheets was obtained by using the same batch of negative electrode sheets and DSP-DP150 stacking machine to stack the positive and negative electrode sheets and assemble them into soft-pack batteries. The 1C / 1C 25℃ room temperature cycle test was carried out. The test results are shown in the figure. Figure 1 shown.

[0089] from Figure 1 It can be seen from the cycle data that comparative examples 1 and 2 use low compaction density, and the cycle capacity retention rates are close to and close to those of experimental examples 2 and 3. After high compaction is used in experimental example 1, the cycle capacity retention rate becomes worse. For experimental examples 4 and 5, the cycle capacity retention rates after high compaction are better than those of the comparative examples, among which the cycle retention rate of experimental example 4 is the best.

[0090] From the above data, it can be seen that the particle size calculation method of the patent of this invention and the particle size grading method with a mass ratio of large particle size to small particle size of 6:4 can achieve high compaction and better cycle life.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The method for preparing a positive electrode material for a sodium ion battery comprises the following steps: (a) preparing material 1 with a Dv50 particle size range of 10-12 μm; (b) Substituting the Dv50 particle size and average area envelope of material 1 into the model formula, the material 2 with a Dv50 particle size range of 5.1-7.5 μm is calculated; (c) preparing material 2 with a Dv50 particle size range of 5.1-7.5 μm; (d) performing particle size grading on the prepared material 1 and material 2 according to a mass ratio; (e) After completing the particle size grading of material 1 and material 2, a positive electrode material for a sodium ion battery is obtained.

2. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: The model formula for calculating the Dv50 particle size of material 2 based on the Dv50 particle size of material 1 in step (b) is as follows: Among them, Dv50 材料1 The 50% median of the volume-accumulated particle size distribution of Material 1, tested using Malvern 3000; Dv50 材料2 The 50% median of the volume cumulative particle size distribution of representative material 2 was tested using Malvern 3000; the average area envelope of material 1 was tested using Keyence VHX-X1; k is the model coefficient, and the k value range is 0.5-2.

0.

3. The method for preparing a positive electrode material for a sodium ion battery according to claim 2, characterized in that: In step (d), the mass ratio of the particle size distribution of material 1 and material 2 is 5:5-9:

1.

4. The method for preparing a positive electrode material for a sodium ion battery according to claim 3, characterized in that: After the positive electrode material of the sodium ion battery in step (e) is made into a positive electrode sheet, the compaction density of the positive electrode sheet is 3.29-3.38 g / cm 3 .

5. A method for preparing a positive electrode material for a sodium ion battery according to claim 2, 3 or 4, characterized in that: The process of preparing material 1 in step (a) comprises: a1) performing a first sintering of the raw materials containing Na, Cu, Fe and Mn elements at 850-920° C. for 6-20 hours, and then performing a first crushing to obtain a sintered material with a particle size of 5 μm ≤ Dv50 ≤ 8 μm; a2) performing a second sintering on the sintered material at 910-940° C. for 6-20 hours at a constant temperature, and then performing a second pulverization to obtain a sodium ion battery positive electrode material with a particle size of 10 μm ≤ Dv50 ≤ 12 μm, that is, obtaining material 1.

6. A method for increasing the compaction density of a positive electrode material for a sodium ion battery according to claim 5, characterized in that: It is characterized in that The process of preparing material 2 in step (c) comprises: c1) performing a first sintering of the raw materials containing Na, Cu, Fe and Mn elements at 850-920° C. for 6-20 hours, and then performing a first crushing to obtain a sintered material with a particle size of 5 μm ≤ Dv50 ≤ 8 μm; c2) The sintered material is subjected to a second sintering at 880-910° C. for a constant temperature sintering time of 6-20 hours, followed by a second pulverization to obtain a sodium ion battery positive electrode material with a particle size of 5.1 μm ≤ Dv50 ≤ 7.5 μm, i.e., obtaining Material 2.

7. The method for preparing a positive electrode material for a sodium ion battery according to claim 6, characterized in that: The raw material containing Na, Cu, Fe and Mn elements in step a1) or c1) also includes element A; the element A includes one or more of Li, Ni, Mg, Zn, Co, Al, Zr and Ti.

8. The method for preparing a positive electrode material for a sodium ion battery according to claim 7, characterized in that: The general formula of the sodium ion battery positive electrode material of material 1 in step a2) is Na a Cu x Fe y Mn z A 1-x-y-z O2, wherein A includes one or more of Li, Ni, Mg, Zn, Co, Al, Zr, Ti; 0.5<a≤1.1, 0.1≤x≤≤0.3, 0<y≤0.5, 0<z≤0.5, 0<1-xyz≤0.

5.

9. A sodium ion positive electrode material obtained by the method for preparing a sodium ion battery positive electrode material according to any one of claims 1 to 8.

10. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 8, or use of the sodium ion positive electrode material according to claim 9 in preparing a positive electrode sheet and a sodium ion battery.

Citation Information

Cited By

  • Preparation method of high-productivity sodium ion battery positive electrode material

    CN121591266A